2017
DOI: 10.1002/jmv.24797
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Epstein‐Barr virus and acute leukemia

Abstract: Infection with Epstein-Barr virus (EBV) may be correlated to the onset of acute leukemia (AL). Studies were performed to investigate the relationship between EBV infection and immunophenotyping of acute lymphoblastic leukemia (ALL) and chromosome aberrations. Additionally, the effects of EBV on clinical prognosis were described. Fluorescence quantitative polymerase chain reaction (FQ-PCR) was used to detect EBV-DNA copy numbers from bone marrow in 110 cases of patients with ALL, 75 cases of patients with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 40 publications
2
21
1
2
Order By: Relevance
“…In our studies, EBV-DNA sequences were found in 88 of the 322 (27.3%) leukemia samples and in 35 of the 106 MDS samples (33%). The frequencies of EBV infection, as described here, were similar to those reported in AL patients (34.6%) and higher than those found in healthy controls (5.4%, 2/37) [8].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our studies, EBV-DNA sequences were found in 88 of the 322 (27.3%) leukemia samples and in 35 of the 106 MDS samples (33%). The frequencies of EBV infection, as described here, were similar to those reported in AL patients (34.6%) and higher than those found in healthy controls (5.4%, 2/37) [8].…”
Section: Discussionsupporting
confidence: 89%
“…Ateyah et al [7] suggested that patients with B-cell acute lymphoblastic leukemia infected with EBV had a significant increase in the expression of CD4+CD25high+ Foxp3+Treg. Several previous investigations have been carried out focusing on the relationship between EBV infection and later leukemogenesis, which seems to play a vital role in the development of ALL [8][9][10][11]. Ahmed et al [9] reported that although EBV infection has no theoretical link with the pathogenesis of AML (EBV infects B lymphocytes), EBV latent membrane protein 1 (LMP1) gene transcripts were found in 5 of 15 (33.3%) patients with AML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Croatia, seroprevalence rates of 91.2% and 97.7% were found among patients with hematological disorders and patients submitted to hemodialysis, respectively [ 68 ]. Guan et al (2017) [ 69 ] studied the correlation between EBV infection and acute leukemia. They reported EBV prevalence rates of 40.9% and 25.3% in patients with acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML), respectively.…”
Section: Prevalence Of CMV and Ebv Infections In Patients With Hemmentioning
confidence: 99%
“…38,39 On the other hand, the most known evidence for previous Epstein-Barr virus infection is associated with the childhood B-ALL. 40 leukemia. [41][42][43][44] Interestingly, among all the differentially expressed miRNAs observed in this study, the most prominent putative biomarker of disease subtype was miR-29c-5p, which was a better discriminator than hsa-miR-708-5p, a reported miRNA with differential expression between childhood T-and B-ALL.…”
Section: Machine Learning and Mirna Expression Validationmentioning
confidence: 99%